2003
DOI: 10.1147/rd.475.0641
|View full text |Cite
|
Sign up to set email alerts
|

Design and validation of a performance and power simulator for PowerPC systems

Abstract: This paper describes the design and validation of a performance and power simulator that is part of the Mambo simulation environment for PowerPC ᭨ systems. One of the most notable features of the simulator, designated as Tempo, is the incorporation of an event-driven power model. Tempo satisfies an important need for fast and accurate performance and power simulation tools at the system level. The power and performance predictions from the simulated model of a PowerPC 405GP (or simply 405GP) were validated aga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 11 publications
0
20
0
Order By: Relevance
“…An initial version of this work that dealt primarily with transaction level power estimation for peripherals appeared in [19]. For modeling the processor power we used the instruction/processor architectural event characterization data derived from real hardware simulations of the PowerPC processor core [16]. That data derived in [16] contained the average power for each architectural event in the processor, where an architectural event corresponds to types of instructions (e.g., load/stores, cache misses, arithmetic instructions).…”
Section: General Power Modeling Approachmentioning
confidence: 99%
See 2 more Smart Citations
“…An initial version of this work that dealt primarily with transaction level power estimation for peripherals appeared in [19]. For modeling the processor power we used the instruction/processor architectural event characterization data derived from real hardware simulations of the PowerPC processor core [16]. That data derived in [16] contained the average power for each architectural event in the processor, where an architectural event corresponds to types of instructions (e.g., load/stores, cache misses, arithmetic instructions).…”
Section: General Power Modeling Approachmentioning
confidence: 99%
“…For modeling the processor power we used the instruction/processor architectural event characterization data derived from real hardware simulations of the PowerPC processor core [16]. That data derived in [16] contained the average power for each architectural event in the processor, where an architectural event corresponds to types of instructions (e.g., load/stores, cache misses, arithmetic instructions). In our approach, as the ISS executes instructions, it calls a callback routine at the completion of each instruction.…”
Section: General Power Modeling Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…Bohrer et al have studied real webserver workloads from sports, e-commerce, financial, and internet proxy cluster and found that average server utilization varies between 11% and 50% [19]. Low utilization has two causes [3]: to guarantee good performance at periods of peak demands, processing capacity is overprovisioned.…”
Section: Introductionmentioning
confidence: 99%
“…Mambo [4] is IBM's full-system simulator which models the PowerPC-based [8] systems, and provides a complete set of simulation tools to help IBM and its partners in pre-hardware development and performance evaluation for future systems [15,1,6,14]. Mambo supports both functional and cycle-accurate simulation modes:…”
Section: Introductionmentioning
confidence: 99%